Analisis Tingkat Ancaman Longsor dI Distrik Ransiki Kabupaten Manokwari Selatan - Alzair, Nur; Mayzarah, Erikha Maurizka (Department Geography Education Faculty of Social Science - Universitas Negeri Jakarta, 2024)
One of the most important activities in landslide risk management is mapping the level of landslide threat. The objective of this research was to map the level of landslide threat in the Ransiki District. This study was carried out in the Ransiki District, South Manokwari Regency, West Papua Province from May to November 2021. Lithology, Geological Structure, Rainfall, Land Use, and Slope were the parameters used in this study. The stack plate method was used, and the analytical hierarchy process (AHP) method was used for parameter weighting. This AHP was used to calculate the weight of each parameter class and landslide disaster parameter. The landslide threat level was mapped using ArcGIS 10.1 software. According to the research findings, there were three levels of landslide threat in the Ransiki District, South Manokwari Regency. The low threat level covered 6,792.06 hectares, or 37.52% of total area of Ransiki District. The Ransiki District has a moderate threat level covered 6,741.33 hectares, or 37.24% of its total area. Ransiki District had a high threat level of 4,567.85 hectares, or approximately 25.24% of its total area. This study provided suggestion that in areas with moderate and high threat levels, more research can be conducted to reduce the impact and losses caused by landslides